The Role of Curcumin on Apoptosis through The RASSF1A and Bax Pathways in Breast Cancer - Nunung Ainur Rahmah; Harliansyah Harliansyah; Fransiscus D. Suyatna; Mpu Kanoko; Primariadewi Rustamadji; Joedo Prihartono; Samuel Johny Haryono; Bethy Suryawati Hernowo (Indonesian Journal of Cancer Chemoprevention, 2020)
Curcumin has been reported with an in vitro the cytotoxic effect on several human cancer cells. However, reports on the mode of action and detail mechanism of curcumin in breast cancer disease are limited. Hence, curcumin’s effect on the human breast cancer cell line MCF-7 and MDA-MB-468 was investigated. The MCF-7 and MDA-MB-468 breast cancer cells line were given curcumin in several doses. The anti-proliferation activity of curcumin was determined using the MTS cell viability test and caspase-3 activity was used to detect apoptosis using flowcytometry. The expression of Ras-association domain family 1 isoform A (RASSF1A) and Bax protein in cells was evaluated by ELISA analysis. Kruskal-Wallis followed by the Mann-Whitney test and the Spearman correlation tests were used to asses correlation among RASSF1A, Bax, and caspase-3. Cytotoxicity of curcumin on MCF-7 was lower than that of MDA-MB-468 (75.73 μg/mL and 380.79 μg/mL). The concentration of curcumin at 80 μg/mL induced apoptosis mainly through the intrinsic pathway by caspase-3 activation. Curcumin also showed an anti-proliferative activity as shown by the increase of RASSF1A and Bax protein. Curcumin mediates anti-proliferative and apoptotic effect through the activation of RASSF1A and Bax. Our research data adds information about the role of curcumin in epigenetic events through RASSF1A protein.Keywords: Bax, caspase-3, curcumin, MCF-7, MDA-MB-468, RASSF1A